Phase Change Memory Device Physics, Reliability and Applications - Redaelli, Andrea; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book describes the physics of phase change memory devices, starting from basic operation to reliability issues. The book gives a comprehensive overlook of PCM with particular attention to the electrical transport and the phase transition physics between the two states. The book also contains design engineering details on PCM cell architecture, PCM cell arrays (including electrical circuit management), as well as the full spectrum of possible future applications.
Chapter 1. Memory overview and PCM introduction -- Chapter 2.Electrical transport in crystalline and amorphous chalcogenides -- Chapter 3.Thermal model and remarkable temperature effects on calcogenide alloys -- Chapter 4.Self-consistent numerical model -- Chapter 5.PCM main reliability features -- Chapter 6.Structure and properties of chalcogenide materials for PCM -- Chapter 7.Material Engineering for PCM Device Optimization -- Chapter 8.PCM scaling -- Chapter 9.PCM device design -- Chapter 10.PCM array architecture and management -- Chapter 11. PCM applications and an outlook to the future.
Keywords: Optical materials; Semiconductors; Electronic circuits; Computer science; Optical Materials; Semiconductors; Electronic Circuits and Systems; Theory of Computation